The Influence of Giving Sadari (Breast Self Examination) Education with Lecture Method on the Implementation of Sadari (Breast Self Examination) on Grade VII and VIII Female Adolescents at SMPN 9 Palangka Raya - Fortuna Fortuna; Eva Prilelli Baringbing; Anggreni Ade Putri (Universitas Ibn Khaldun Bogor, 2026)
SADARI (Breast Self-Examination) is an important early detection method for breast cancer since adolescence. However, many young women are unaware of it and do not practice SADARI routinely. Objective: To determine the influence of SADARI education with the lecture method on the implementation of SADARI (Breast Self-Examination), among female adolescents in grades VII and VIII at SMPN 9 Palangka Raya. Methods: The design of this research was pre-experimental with one-group pretest-posttest design. The research sample consisted of 60 people selected using simple random sampling techniques. The data were collected using questionnaires and analyzed using the Wilcoxon Signed Rank Test. Results: The results of the statistical test using the Wilcoxon test obtained a p value (0.000) with p < 0.05, so Ha was accepted, so that there was a significant influence of providing SADARI (Breast Self-Examination) education using lecture method on the of SADARI (Breast Self-Examination) on grade VII and VIII female adolescents at SMPN 9 Palangka Raya. Conclusion: BSE education with lecture methods was effective in increasing BSE knowledge and practice in adolescent girls. Educational programs like this need to be implemented regularly in schools. It was expected that schools could make SADARI (Breast Self-Examination) education materials as part of the UKS program and health curriculum, as well as hold routine counseling activities to instill early detection habits from an early age.